E-commerce: the challenge of virtual permanent establishments - Adlkofer, Michelle Leigh,Venter, Michelle (Rhodes University, Faculty of Commerce, Department of Accounting, 2015)
The continued growth of world commerce has led to the advance of the permanent establishment principles. These principles are, however, constantly challenged by the developments of e-commerce. This thesis considers the taxing of a permanent establishment and the influence of e-commerce on the concept of a permanent establishment. In 2000, the Organisation for Economic Co-operation and Development ("OECD" ) developed and introduced guidelines on how to deal with e-commerce in the context of a permanent establishment. Since the OECD guidelines on e-commerce were issued, the permanent establishment principles have come under further scrutiny. The latest development came about in 2013 with the release of the Base Erosion and Profit Shifting ("BEPS" ) Action Plan. This Action Plan addresses the intention of the OECD to deal with the taxing of the digital economy. With the development of e-commerce and the result of e-commerce creating intangible boundaries between countries, the concept of a virtual permanent establishment has emerged. This has resulted in the need to tax a presence of an enterprise in a jurisdiction where no actual physical connection can be established. Various authors have made suggestions on how to ensure that an economy in which business is being carried on is correctly compensated for in the form of taxes. The source of income is the driving force for the imposition of taxation today. The main goal of this thesis was to explore the alignment of the concepts of a permanent establishment and e-commerce in the digital economy. This study therefore examined the concepts of both permanent establishments and e-commerce, and explored authors' views and suggestions on how to deal with the inter-related effects of these two concepts. The relevant Action Points in the OECD Action Plan were also considered.,Maiden name: Venter, Michelle
Keywords: Organisation for Economic Co-operation and Development; Electronic commerce; Electronic commerce -- Taxation; Double taxation -- Treaties; Globalization